Receptiveness to innovation during the COVID-19 pandemic: asymmetries in the adoption of digital routines - Anna A. Mikhaylova; Andrey S. Mikhaylov; Dmitry V. Hvaley (Regional Studies, Regional Science, 2021)
The COVID-19 pandemic has had an unprecedented impact on both national economies and everyday life. Massive lockdowns and a shift towards digital technologies forced people to adapt to technological innovations in their daily routines in a new online format. In this study we identify patterns of change in the population’s adoption of and receptiveness to digitalization. The focus is on registering the expansion of digital routines influenced by the coronavirus depending on the place of residence, infrastructure and demographics. The results of a population survey held in August 2020 across all municipalities of the Kaliningrad region of Russia suggest that the magnitude of the pandemic’s effect in accelerating digitalization is different for various population types. Most receptive to digital innovations are residents of economically developed municipalities aged 26–40 with higher education having a stable Internet connection at a fair price. The article presents a typology of municipalities on the adoption of and receptiveness to innovation. It is shown that without the established infrastructure, technological, economic, cultural and behavioural basis, the acceleration of digitalization does not occur.